Composition and Distribution of Income: a Study of Rural Household in Haryana. - Punam (2010)
The problem of economic disparities (measured in terms of income, assets and consumption distribution) is as old as the history of mankind. Economic and social development is a bi-parental term. Therefore economic and social disparities are mutually reinforcing socially residual groups and the economically marginalized remain socially residual. It implies a disproportionate distribution of economic gains among different social groups. Economic development precedes the socially residual groups gain marginally, which is not sufficient for them to make both ends meet. In India sincere efforts are made to overcome this problem right from the adoption of growth with social justice. But the fruits of development are largely reaped by the big farmers, leading industrialists and the powerful groups in society. During independence, considerable differences in economic development of different categories of the country existed. One of the main objectives of the planning process initiated in the early 1950s was to reduce these economic differences and to achieve economically balanced development. The present study has been devoted to examine the state of economic disparities (measured in terms of income distribution and many other socio-economic factors ; number of earners, age of the chief earner, education of the chief earner and size of the family) in rural Haryana. The study is spread over 8 districts, 16 villages and 480 households comprising farm households, salary earners, labour household and self-employed non-farm household.